Research category "innovation potential" - Pererva, P. G.; Veryutina, Victoria; Peredriy, Andrea Elizabet (My University, 2022)
It has been proven that innovation potential is a complex of economic, organizational and social factors that determine the ability of an object (industry, region or organization) to independently create innovations, to perceive other innovations created outside the object, to interact with other objects for common creation. and (or) the use of innovations, as well as to get rid of the obsolete in the existing socio-economic and organizational conditions.
Keywords: innovative potential; assessment; forecasting; use; business; enterprise